Effects on electrical characteristics of commercially available Si and GaAs diodes exposed to Californium-252 radiation - Che Omar, Nuurul Iffah; Hasbullah, Nurul Fadzlin; Alang Md Rashid, Nahrul Khair; Abdullah, Jaafar (2012)
The aim of this research is to investigate the effects of neutron irradiation using Cf-252 neutron source on different types of commercially available Si and GaAs diodes. Pre and post irradiation effects are compared by analyzing their respective forward bias (FB) and reverse bias (RB) current-voltage (I-V) characteristics. It was discovered that, at low neutron dose of up to 178.63mSv, the electrical characteristics of silicon diodes improved as indicated by a reduction in FB and RB leakage current, ideality factor and series resistance. However, GaAs diodes show a significant leakage current increment in RB which is interpreted as being due to damage displacement.